From conventional to Delay Doppler altimetry: A demonstration of continuity and improvements with the Cryosat-2 mission. Issue 6 (15th September 2018) - Raynal, M.; Labroue, S.; Moreau, T.; Boy, F.; Picot, N.
Abstract: Cryosat-2 is the first satellite that embarks an altimeter able to operate in several modes. Among them, the Synthetic Aperture Radar mode (SARM) also referred to as Delay Doppler mode is expected to improve the measurement resolution and precision. Based on a two year time series, this paper presents the SARM assessment over ocean. It demonstrates the seamless transition, below the centimeter level, between conventional pulse-limited and Delay Doppler altimetry at long wavelength for the sea level. Nevertheless, the SARM retrieved Significant Wave Height (SWH) is biased by 20 cm and depends on the sea state. This paper also confirms that, thanks to the better signal to noise ratio and along track resolution brought by the SARM, the small scales observability is significantly improved with respect to the Low Resolution Mode (LRM). The SARM Sea Level reveals a spectral slope never observed for wavelength below 30 km that is not yet explained. Further analyses at global scales using the Sentinel-3A dataset will certainly help to characterize the source of this signal.